2003
DOI: 10.1258/135763303322196286
|View full text |Cite
|
Sign up to set email alerts
|

A multidisciplinary approach to the treatment of eating disorders via videoconferencing in north-east Scotland

Abstract: Until recently many remote communities in Scotland, especially on the northern islands, were unable to access specialist eating disorder services. The Grampian Eating Disorder Service, based in the north-east of Scotland, has developed a video-therapy service that offers specialist psychological and nutritional therapy for sufferers of eating disorders. Twelve patients have been treated via videoconferencing. Patients consistently rated high levels of satisfaction with all aspects of video-therapy, and after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 3 publications
(1 reference statement)
0
32
0
Order By: Relevance
“…67 In a small number of reports specifically involving a psychologist, CBT was provided to isolated Scottish communities via videoconferencing. 68,69 Most patients were satisfied with the approach, although there were complaints that poor sound and picture quality distracted from the communication. Similar treatment outcomes are reported with face-to-face, two-way audio and videoconferencing.…”
Section: Remote Counselling Via Videoconferencingmentioning
confidence: 98%
“…67 In a small number of reports specifically involving a psychologist, CBT was provided to isolated Scottish communities via videoconferencing. 68,69 Most patients were satisfied with the approach, although there were complaints that poor sound and picture quality distracted from the communication. Similar treatment outcomes are reported with face-to-face, two-way audio and videoconferencing.…”
Section: Remote Counselling Via Videoconferencingmentioning
confidence: 98%
“…In studies without a comparison group, researchers often concluded that users were generally satisfied when engaging in psychotherapy over telemedicine Myers, Valentine, & Melzer, 2008;Simpson, Bell, & Britton, 2006;Simpson et al, 2003;Simpson et al, 2002), and studies that compared VC to in-person psychotherapy reported similar satisfaction levels between the conditions (Cluver et al, 2005;King et al, 2009;Morgan et al, 2008;Nelson, Barnard, & Cain, 2003;Ruskin et al, 2004). When sources of dissatisfaction arose, they primarily involved technical challenges, but such issues appeared to have little impact on overall satisfaction levels (e.g., Cowain, 2001;).…”
Section: Satisfaction (Question 9)mentioning
confidence: 99%
“…It was not always clear from the written reports when samples were overlapping, which would result in an apparent inflation in the quantity of studies. In fact, only 42 unique samples were studied and only 21% of those Bulimia nervosa Absence of binge/purge at follow-up EU Goldfield & Boachie, 2003 Anorexia nervosa (ϩ) Weight EU Improved medical condition Simpson et al, 2003 Eating disorders (Ϫ) Symptoms EU (ϩ) Nutritional knowledge (ϩ) Nutritional content of diet Simpson et al, 2006 Bulimia nervosa (Ϫ) Binging (for half (6) had subjects randomized to condition. Moreover, some studies reported nonmanualized or blended interventions (e.g., psychotherapy and pharmacotherapy; individual and group therapy) and mixed diagnostic groups.…”
Section: Types Of Articles (Question 1)mentioning
confidence: 99%
“…Supervision may be done either in real-time with the supervisor present via videoconferencing, or, when appropriate, by the use of store and forward technology. 26 Supervising practitioners shall comply with professional requirements for in-person supervision of Registrars, interns and other staff providing mental health care.…”
Section: • Multidisciplinary Team Management (Mdt)mentioning
confidence: 99%